Ideology and Impact of the Feminism Movement in Indonesia Beginning of the XX Century - Faras Puji Azizah; Egi Hadi Kusnadi; Dede Dwi Kurniasih; Sudarman Sudarman; Erman Erman (UIN Imam Bonjol Padang, 2024)
This article aims to describe the feminist movement in Indonesia in the early 20th century. This research employed the historical method, encompassing several key stages. Heuristics involved the systematic gathering of relevant sources, including articles, books and existing research related to the study. Subsequently, source criticism was conducted to assess the authenticity, reliability and credibility of the identified sources. Following this, the interpretation stage involved analyzing the collected data to extract meaningful insights and draw conclusions. Finally, the findings were combined and presented in a scholarly format through the writing of a research paper. In addition, the author collects data through the Dutch website (Delpher) which is a website that provides digitized full texts of newspapers, books, journals, and copy sheets of historic Dutch-language radio news broadcasts. The research reveals that the Indonesian feminist movement arose in response to the injustices faced by women during Dutch colonial rule in the East Indies. A key example of this inequality was the restricted access to education for women compared to their male counterparts. This disparity spurred the emergence of the feminist movement, driven by the goal of securing equal rights for women.